2013
DOI: 10.1021/ef400573p
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Supercritical Water in Pyrolysis of Carbonaceous Compounds

Abstract: Supercritical water (SCW) has been studied widely for upgrading complex and low-value carbonaceous materials due to its ability to depress coke formation and improve product quality. Many researchers attributed these effects to SCW’s hydrogen donation ability, including H• and H+, while others to physical effects, such as the cage effect or the solvent effect. To clarify the role of SCW, three probe compounds, naphthalene, p-benzoquinone, and azobenzene, are treated individually in SCW at 400 °C and 25.3 MPa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The position of the new band is in excellent agreement with that of HQ in Figure a and the calculated spectra (vide infra). This finding is in good agreement with the that from the studies by Razimov et al and Xu et al However, the conversion is faster in hot compressed acid media, only a few seconds are required to convert BQ to HQ and other nonabsorbing condensation products at 473 K, and the yield of HQ is also extremely low when compared to that reported by Xu et al, 60% of BQ conversion after 2 h and a 37% HQ yield in SCW.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The position of the new band is in excellent agreement with that of HQ in Figure a and the calculated spectra (vide infra). This finding is in good agreement with the that from the studies by Razimov et al and Xu et al However, the conversion is faster in hot compressed acid media, only a few seconds are required to convert BQ to HQ and other nonabsorbing condensation products at 473 K, and the yield of HQ is also extremely low when compared to that reported by Xu et al, 60% of BQ conversion after 2 h and a 37% HQ yield in SCW.…”
Section: Resultssupporting
confidence: 92%
“…1 On the other hand, other studies have shown that BQ, the oxidation product of HQ, readily decomposes in the presence of water at relatively low temperatures. 2,3 For instance, Razimov et al 3 found that BQ polymerizes in water at temperatures as low as 323 K, with the formation of HQ. Because BQ is stable in organic solvents below 493 K and does not undergo thermal bulk polymerization, the authors concluded that the process requires the presence of H 2 O or hydroxyl ions to initiate the polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective extraction of coke precursors and upgraded products from the oil phase at fast rates using column flow reactors, not only suppressed the coke formation, but also promoted the upgrading of bitumen. Xu et al [78] confirmed that SCW could not donate H• and HO• radicals as no products formed from the reaction of HO• with three compounds, naphthalene, p-benzoquinone, and azobenzene, under SCW conditions. The different product distribution under the SCW conditions from the inert atmosphere was closely related to the increased solvent dispersion of radicals.…”
Section: Mechanisms Of Hydrocarbons Transformationmentioning
confidence: 97%
“…Therefore, SCW was not considered to behave as a radical capping agent supplying hydrogen to liquid products; that is, the chemical effect of SCW was negligible. A recent study using pure compounds also refuted the chemical effect of SCW 14) . Figure 5 explains conceptually the effect of reactant dispersion on product properties.…”
Section: Summary Of Scw Effectmentioning
confidence: 98%